Transcriptome Profile Changes Associated With Heat Shock Reaction in the Entomopathogenic Nematode, Steinernema carpocapsae - Xie, Yi-Fei; Wang, Xiu-Dan; Zhong, Wu-Hong; Zhu, Dao-Hong; He, Zhen (Frontiers in Physiology, 2020)
The entomopathogenic nematode Steinernema carpocapsae has been used for control of soil insects. However, S. carpocapse is sensitive to environmental factors, particularly temperature. We studied a S. carpocapse group that was shocked with high temperature. We also studied the transcriptome-level responses associated with temperature stress using a BGIseq sequencing platform. We de novo assembled the reads from the treatment and control groups into one transcriptome consisting of 43.9 and 42.9 million clean reads, respectively. Based on the genome database, we aligned the clean reads to the Nr, GO and KEGG databases and analyzed the differentially expressed genes (DEGs). Compared with the control, the heat-shocked group had significant differential expression of the heat-shock protein (HSP) family, antioxidase (GSTs and SOD), monooxygenase (P450) and transcription factor genes (DAF-16 and DAF-2). These DEGs were demonstrated to be part of the Longevity pathway and insulin/insulin-like signaling pathway. The results revealed the potential mechanisms, at the transcriptional level, of S. carpocapsae under thermal stress.